2016
DOI: 10.1093/brain/aww012
|View full text |Cite
|
Sign up to set email alerts
|

Motor cortex and hippocampus are the two main cortical targets in LGI1-antibody encephalitis

Abstract: Ã These authors contributed equally to this work. Encephalitis associated with antibodies against leucine-rich glioma-inactivated 1 (LGI1) protein is increasingly recognized as an auto-immune disorder associated with characteristic tonic-dystonic seizures. The cortical or subcortical origin of these motor events is not clear. Some patients also present with different epileptic seizures and with cognitive impairment. The frequency of these features and their timing during the natural history of this encephaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

25
167
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(196 citation statements)
references
References 28 publications
25
167
1
3
Order By: Relevance
“…Characteristic unilateral frontal slow EEG potentials, which preceded the contralateral tonic-dystonic seizures, were recorded in all seven tested patients. The FDG-PET confirmed hypermetabolism in primary motor cortex contralateral to the affected limb [71]. The LGI1 antibodies seem to have two main cortical targets: the motor cortex and the hippocampus.…”
Section: Anti-vgkc Antibody-associated Encephalitismentioning
confidence: 74%
“…Characteristic unilateral frontal slow EEG potentials, which preceded the contralateral tonic-dystonic seizures, were recorded in all seven tested patients. The FDG-PET confirmed hypermetabolism in primary motor cortex contralateral to the affected limb [71]. The LGI1 antibodies seem to have two main cortical targets: the motor cortex and the hippocampus.…”
Section: Anti-vgkc Antibody-associated Encephalitismentioning
confidence: 74%
“…A recent FDG-PET analysis reported hypermetabolism of the sensorimotor cortex in patients with anti-LGI1 encephalitis that, together with contralateral frontal EEG changes and results from polymyographic recordings, are suggestive of a motor cortex origin of FBDS 5. Another FDG-PET study observed hypermetabolism in the precentral gyrus, basal ganglia and cerebellum in patients with LGI1 encephalitis with FBDS 16.…”
Section: Discussionmentioning
confidence: 98%
“…They have shown that most patients with diffuse cerebral hypometabolism had clinical syndromes consistent with encephalitis (72.2% patients) (34). However, a heterogeneous pattern of brain metabolism has been reported on the brain 18 F-FDG PET/CT of patients with AE so far (34)(35)(36)(37)(38). Some previous case reports described hypermetabolism of cerebral cortices or striatum as a predominant feature of autoimmune encephalitides (35,(37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%